2008
DOI: 10.2172/1324728
|View full text |Cite
|
Sign up to set email alerts
|

Size Effect in Continuum Modeling

Abstract: The mechanical properties of some materials (Cu, Ni, Ag, etc.) have been shown to develop strong dependence on the geometric dimensions, resulting in a size effect. Several theories have been proposed to model size effects, but have been based on very few experiments conducted at appropriate scales. Some experimental results implied that size effects are caused by increasing strain gradients and have been used to confirm many strain gradient theories. On the other hand, some recent experiments show that a size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The work hardening behavior of the copper wires will make significant difference in their yield strength. In this study we ensured all wire specimens in elasticity before torsional loading according to previous study in tensile response of the copper wires [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The work hardening behavior of the copper wires will make significant difference in their yield strength. In this study we ensured all wire specimens in elasticity before torsional loading according to previous study in tensile response of the copper wires [3].…”
Section: Discussionmentioning
confidence: 99%
“…The EBSD results in Ref. [3] showed that the microstructures of these copper wires are quite similar: many annealing twins but no significant texture present. The larger-size wire has a larger average grain size but still at the same order of magnitude for all copper wires.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations